Tafsir Islam Moderat di Media Sosial: Revitalisasi Syiar dan Kontestasi Narasi - Lukman Fajariyah; Abd. Halim (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
This study scrutinizes the dynamic interpretation and contestation of Islamic moderation (wasatiyah) on social media platforms. Amidst the rapid proliferation of moderation campaigns and diverse posts, the research systematically analyzes content using hashtags like #Islamwasathiyah, #wasathiyah, #moderasiberagama, #moderasi and #ayatayatmoderasi. The findings unveil intricate interpretations of moderation, encompassing both textual and contextual dimensions. Notably, the contested nature of moderation becomes apparent as proponents associate it with human brotherhood, tolerance, and the ideal Muslim attitude, while opponents view it as indicative of an unserious commitment or a half-hearted approach to Islam. These divergent perspectives, influenced by individual backgrounds and educational levels, significantly contribute to the broader discourse on religious moderation narratives within the dynamic discourse of social media.